Defining the learning curve for endotracheal intubation in the emergency department - Gun Tak Lee; Jong Eun Park; Sook-young Woo; Tae Gun Shin; Daun Jeong; Taerim Kim; Se Uk Lee; Hee Yoon; Sung Yeon Hwang (Scientific Reports, 2022)
Abstract To determine the minimum number of endotracheal intubation (ETI) attempts necessary for a novice emergency medicine (EM) trainee to become proficient with this procedure. This single-center study retrospectively analyzed data obtained from the institutional airway registry during the period from April 2014 to March 2021. All ETI attempts made by EM trainees starting their residency programs between 2014 and 2018 were evaluated. We used a first attempt success (FAS) rate of 85% as a proxy for ETI proficiency. Generalized linear mixed models were used to evaluate the association between FAS and cumulative ETI experience. The number of ETI attempts required to achieve an FAS rate of ≥ 85% was estimated using the regression coefficients obtained from the model. The study period yielded 2077 ETI cases from a total of 1979 patients. The FAS rate was 78.6% (n = 1632/2077). After adjusting for confounding factors, the cumulative number of ETI cases was associated with increased FAS (adjusted odds ratio, 1.010 per additional ETI case; 95% confidence interval 1.006–1.013; p < 0.001). A minimum of 119 ETI cases were required to establish a ≥ 85% likelihood of FAS. At least 119 ETI cases were required for EM trainees to achieve an FAS rate of ≥ 85% in the emergency department.